If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(x + -1) = 4x + -16 Reorder the terms: -6(-1 + x) = 4x + -16 (-1 * -6 + x * -6) = 4x + -16 (6 + -6x) = 4x + -16 Reorder the terms: 6 + -6x = -16 + 4x Solving 6 + -6x = -16 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 6 + -6x + -4x = -16 + 4x + -4x Combine like terms: -6x + -4x = -10x 6 + -10x = -16 + 4x + -4x Combine like terms: 4x + -4x = 0 6 + -10x = -16 + 0 6 + -10x = -16 Add '-6' to each side of the equation. 6 + -6 + -10x = -16 + -6 Combine like terms: 6 + -6 = 0 0 + -10x = -16 + -6 -10x = -16 + -6 Combine like terms: -16 + -6 = -22 -10x = -22 Divide each side by '-10'. x = 2.2 Simplifying x = 2.2
| 5.4x=9.0 | | 4x-1+1=2x+13+1 | | X+0.07x=58.85 | | -5/2v=20 | | m/8=8.3333333333333333333333333333 | | 3x+20=x^3 | | f(5)=3x^2-2x+1 | | x+8.1=2.7 | | 4(7x-1)=3(2x+1) | | 1/6-5/6 | | (5)/(12)*(6xy-10x^(2)y)-(3)/(4)y(3x^(2)-2x^(2)) | | 8+16x=-32+12x | | 3b+2c+5=a-9 | | y/3-4=-5 | | 3y^2-13-10=0 | | -5x+8y=-6 | | a+c-6b=4b+3c-3 | | 18+9cos(2x)-27cos(x)=0 | | (150x-3x^2)=1900 | | 2x^2+2xy+y^2=10 | | 2b(2b-5)=0 | | 35x^2-20x=0 | | (x^4y^5)^3/2 | | 5y+7-3-8y=37 | | 5(2+c)=6(2+c) | | -9x=-56 | | 2(2x+1)-2(5-x)=29 | | 3x-(1/5)-(x/7)=3 | | 5x^2-22x+6=-2 | | 8/(2x) | | 5x^2-22x+6=0 | | 45.00+x=68.88 |